PENGARUH REBUSAN BIJI ALPUKAT TERHADAP PENURUNAN GULA DARAH - Yuli Astuti (Jurnal Medika Hutama, 2022)
Diabetes Mellitus is a disease caused by an increase in blood sugar (glucose) levels. Increased glucose in the blood can occur because the hormone insulin does not succeed in bringing our glucose into the body's cells. The prevalence of patients with diabetes in Indonesia reaches 6.2%, which means that there are more than 10.8 million people suffering from diabetes per year 2020. One of the nursing problems for patients with diabetes mellitus is the lack of knowledge about Diabetes Mellitus. The study was conducted from 26 July-1 August 2021. The intervention carried out was to provide therapy with avocado seed boiled water to reduce blood sugar level of people with diabetes mellitus for 7 days. Data collection techniques used are interviews, observation and documentation. with a total of 6 respondents who were given avocado seed boiled water. The average difference between the values ​​before and after the intervention was 36. The paired t-test test obtained a significant value of 0.0005 (p <0.05), which means that there is an effect of giving avocado seed boiled water to decrease blood sugar level in type II Diabetes Mellitus patients.